Good neighbors : a novel - Langan, Sarah (Atria Books, 2021)
"From three-time Bram Stoker-Award-winning novelist Sarah Langan comes a propulsive literary suburban noir set in near-future America during the hottest summer on record. Maple Street has a neighborly cul-de-sac, where a terrible secret tears a rift between two misfit moms who were once best friends. When innocent Shelly Schroeder falls down a sinkhole, it's one mom's word against the other's, in a court of public opinion that can end only in blood. Think Big Little Lies-if reimagined by Shirley Jackson"--